(3OSJhQ GddZIs - (3CHh YHO Gddg GdMSjf Hf EHQGgje Hf CMeO GdfWfRis; (3YHjOGddg fYeGf GdUdGMjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdYGde hHYO agPG OSJhQ GddZI GdYQHjI GdeSJYedI MQQgG GdTjN GdCOjH CHh YHO Gddg GdMSjf hbGd bSeJgG Ydi KeGfjI hYTQjf HGHkG s
(3BNQgG (B:s
(3GdEeGdI NeSI YTQ jLeYgG KhH HjJ jLeY GdMQha cdgG Je GdcJGH HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eOjfI GdYde (B_ (3GdcGXejI (B(245) s
Keywords: (3GdeLGejYs